Advances in AAV-mediated gene replacement therapy for pediatric monogenic neurological disorders - Livia Zhou; Yafeng Wang; Yiran Xu; Yaodong Zhang; Changlian Zhu (Molecular Therapy: Methods & Clinical Development)
Pediatric monogenetic diseases encompass a spectrum of debilitating neurological disorders that affect infants and children, often resulting in profound cognitive and motor impairments. Gene replacement therapy holds immense promise in addressing the underlying genetic defects responsible for these conditions. Adeno-associated virus (AAV) vectors have emerged as a leading platform for delivering therapeutic genes due to their safety profile and ability to transduce various cell types, including neurons. This review highlights recent advancements in AAV-mediated gene replacement therapy for pediatric monogenetic diseases, focusing on key preclinical and clinical studies. We discuss various strategies to enhance transduction efficiency, target specificity, and safety. Furthermore, we explore challenges such as immune responses, along with innovative approaches to overcome these obstacles. Moreover, we examine the clinical outcomes and safety profiles of AAV-based gene therapies in pediatric patients, providing insights into the feasibility and efficacy of these interventions. Finally, we discuss future directions and potential avenues for further research to optimize the therapeutic potential of AAV-delivered gene replacement therapy for pediatric encephalopathies, ultimately aiming to improve the quality of life for affected individuals and their families.